A Fault-Tolerant Agent-Based Architecture for Transient Servers in Fog Computing - Neto, Jose Pergentino de Araujo; Pianto, Donald M.; Ralha, Celia G. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2018: Anais do XXX International Symposium on Computer Architecture and High Performance Computing, 2018)
Cloud datacenters are exploring their idle resources and offering virtual machine as transient servers without availability guarantees. Spot instances are transient servers offered by Amazon AWS, with rules that define prices according to supply and demand. These instances will run for as long as the current price is lower than the maximum bid price given by users. Spot instances have been increasingly used for executing computation and memory intensive applications. By using dynamic fault tolerant mechanisms and appropriate strategies, users can effectively use spot instances to run applications at a cheaper price. This paper presents a resilient multi-strategy agent-based cloud computing architecture. The architecture combines machine learning and a statistical model to predict instance survival times, refine fault tolerance parameters and reduce total execution time. We evaluate our strategies and the experiments demonstrate high levels of accuracy, reaching a 94% survival prediction success rate, which indicates that the model can be effectively used to define execution strategies to prevent failures at revocation events under realistic working conditions.